Compartmental analysis of retinal vascular parameters and thickness in myopic eyes using SS-OCTA - Zeng, Chen; Tang, Chong; Tan, Yixin; Liu, Juxian; Shi, Kai; Li, Qi (Frontiers in Medicine, 2024)
BackgroundThis study aimed to comprehensively explore the thickness and topographic distributions of retinal vessel alterations of different myopic eyes by using swept-source OCT angiography (SS-OCTA).MethodsOne hundred myopes were included in this observational cross-sectional study. All participants underwent a series of ocular examinations of biometrical parameters, including spherical equivalent refraction (SER), axial length (AL), intraocular pressure (IOP), curvature radius (CR), and others. Retinal parameters like vessel density (VD) of different compartments of papillary and peripapillary sectors were measured by SS-OCTA, respectively. Two sample-independent T-test was applied to identify intraocular differences in retinal biometrical indicators between groups, and correlation analysis was used to explore potential relationships between AL/CR ratio and some ocular variables.ResultsFor high myopic participants, they exhibited a lower vessel density, a lower small vessel density, and a lower flow area, especially in the superficial layer and the nerve fiber layer (RNFL), along with a thinner superficial layer, RNFL and retina. More alterations were proved in nasal peripapillary sectors in high myopes. We also explored their hidden relationship with AL/CR ratio. We found that in non-high myopes, the thickness of the whole retina, RNFL and the superficial layer were all negatively correlated with AL/CR ratio in the papillary and peripapillary zone. In contrast, the vessel density and flow area of several vessel layers were positively correlated. However, there wasn’t so much significance found in high myopic eyes.ConclusionRetinal vessel microstructure was more easily affected in highly myopic eyes, especially in superficial blood vessels, and compartmental analysis showed that alterations in nasal peripapillary sectors were more evident. Additionally, we highlighted hidden correlations between AL/CR ratio and blood flow characteristics of specific vascular layers, which could serve as sensitive biometrical indicators of early retinal damages.